6 Clinical presentation and outcomes of childhood hypertrophic cardiomyopathy associated with friedreich's ataxia: a national cohort study. (4th June 2021) - Rance, Thomas; Norrish, Gabrielle
Abstract : Introduction: Hypertrophic cardiomyopathy (HCM) is a common manifestation and important predictor of morbidity and mortality in children with Friedreich's ataxia (FA). HCM is present in up to 85% of FA patients however despite this, the clinical spectrum and phenotype is poorly described in children. This has important implications for long-term follow-up and management of children with this disease. The aim of this study was to describe the clinical characteristics and outcomes in a well-characterised longitudinal cohort of children with FA-HCM in the United Kingdom (UK) over four decades. Methods: Demographic and clinical data for all children (<18 years) diagnosed with FA-HCM between 1980-2017 were retrospectively collected from 11 out of 13 UK paediatric cardiology centres. Results: 78 patients with FA-HCM were identified (male n=45, 58%) with a mean age at baseline evaluation of 10.9 years (± 3.1). HCM diagnosis was within one year of cardiac referral in 29 (69.4%), but preceded the diagnosis of FA in 4 (5.3%). At baseline, 65 (90.3%) had concentric left ventricular (LV) hypertrophy with a mean maximal left ventricular wall thickness 12.8mm (± 2.6, range 8-19mm). Six patients (12.5%, n=49) had LV systolic impairment. Over a median follow up of 5.1 years (IQR 2.4-7.3), eight (10.5%) had documented supraventricular arrhythmias [atrial fibrillation (n=3), atrial flutter (n=1), atrial ectopic tachycardia (n=1) and unspecified supraventricular tachycardia (n=3)] and four (7.8%) had non-sustained ventricular tachycardia. There were no differences in baseline clinical characteristics between patients with and without atrial arrhythmias, but a higher proportion had impaired systolic function at last clinical review (n=3, 37.5% vs n=1, 1.4%, p value <0.001). Forty (56.3%) were started on medications for cardiac symptoms, one underwent cardiac transplantation (aged 4 years, prior to diagnosis of FA) and 8 patients (10.6%) died [atrial-arrhythmia related (n=2); heart-failure related (n=1); non-cardiac (n=2); or unknown cause (n=3)]. There were no sudden cardiac deaths. Freedom from death or transplantation at 10 years was 80.8% (95% CI 62.5-90.8). No demographic or baseline clinical characteristics, including MLVWT at baseline, predicted transplant-free survival on univariable analysis ( table 1 ). Conclusions: This national study of childhood FA-HCM is the largest cohort reported to date and describes a high prevalence of atrial arrhythmias and early progression to end-stage disease. Overall mortality is similar to that reported in non-syndromic childhood HCM but no patients died suddenly. Conflict of Interest: None